2003
DOI: 10.1046/j.1365-2249.2003.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CD4+CD25+ regulatory T cells is associated with a loss of regulation leading to increased pathology in Helicobacter pylori-infected mice

Abstract: SUMMARYHelicobacter pylori induces symptomatic chronic gastritis in a subpopulation of infected individuals. The mechanism(s) determining the development and severity of pathology leading to symptoms are not fully understood. In a mouse model of H. pylori infection we analysed the influence of immunoregulatory CD4 + CD25 + T cells on H. pylori colonization and gastritis. Athymic C57BL/6 nu/nu mice were reconstituted with (a) lymph node (LN) cells (b) LN cells depleted of CD25 + T cells (CD25 -LN) or (c) not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
120
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 31 publications
11
120
3
Order By: Relevance
“…Kandulski et al reported that H. pylori-induced gastritis is associated with a recruitment of naturally occurring FOxP3(+) Treg cells that correlate with higher bacterial colonization and increased mucosal TGFβ1 expression, suggesting that H. pylori infection suppresses the maintenance and aggravation of gastric inflammation by activating the TGFβ1-FoxP-CD4 + CD25 high Treg pathway (16). A similar phenomenon was observed in other animal studies (17,18). Based on the above studies, we inferred that TGFβ1 plays an important role in the inhibition of H. pylori-induced gastritis.…”
Section: Discussionsupporting
confidence: 56%
“…Kandulski et al reported that H. pylori-induced gastritis is associated with a recruitment of naturally occurring FOxP3(+) Treg cells that correlate with higher bacterial colonization and increased mucosal TGFβ1 expression, suggesting that H. pylori infection suppresses the maintenance and aggravation of gastric inflammation by activating the TGFβ1-FoxP-CD4 + CD25 high Treg pathway (16). A similar phenomenon was observed in other animal studies (17,18). Based on the above studies, we inferred that TGFβ1 plays an important role in the inhibition of H. pylori-induced gastritis.…”
Section: Discussionsupporting
confidence: 56%
“…Treg appear to induce anergy of gastric CD4 1 T cells by interfering with the costimulation of TCR in a mechanism that depends on CTLA-4 expression by Treg [51]. In mice, adoptive transfer of CD4 1 T cells depleted of the Treg subset in athymic nu/nu mice leads to decreased H. pylori numbers after challenge, and increased inflammation compared with transfer of both CD4 1 T cells and Treg [52]. Depletion of Treg in C57BL/6 mice infected with H. pylori resulted in increased gastritis and reduced bacterial numbers and a strong Th1 response [19].…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to suppression of immune responses by regulatory T (Treg) cells. Recent studies have shown that Treg cells can restrict memory CD8+ T cell responses and suppress inflammation [41,42]. Furthermore, it has been shown that Treg cells express toll-like receptor 4 (TLR-4) and are activated by LPS [43].…”
Section: Discussionmentioning
confidence: 99%